Nidogen-1 is a novel extracellular ligand for the NKp44 activating receptor. (2nd September 2018) - Gaggero, Silvia; Bruschi, Maurizio; Petretto, Andrea; Parodi, Monica; Zotto, Genny Del; Lavarello, Chiara; Prato, Carola; Santucci, Laura; Barbuto, Alessandra; Bottino, Cristina; Candiano, Giovanni; Moretta, Alessandro; et al.
ABSTRACT: The release of soluble ligands of activating Natural Killer (NK) cell receptors may represent a regulatory mechanism of NK cell function both in physiologic and in pathologic conditions. Here, we identified the extracellular matrix protein Nidogen-1 (NID1) as a ligand of NKp44, an important activating receptor expressed by activated NK cells. When released as soluble molecule, NID1 regulates NK cell function by modulating NKp44-induced IFN-γ production or cytotoxicity. In particular, it also modulates IFN-γ production induced by Platelet-Derived Growth Factor (PDGF)-DD following NKp44 engagement. We also show that NID1 may be present at the cell surface. In this form or when bound to a solid support (bNID1), NID1 fails to induce NK cell cytotoxicity or cytokine release. However, analysis by mass spectrometry revealed that exposure to bNID1 can induce in human NK cells relevant changes in the proteomic profiles suggesting an effect on different biological processes.